Improving physician wellness through electronic health record education. (September 2021) - Johnson, Elizabette; Roth, Elizabeth
Objective: Our goal is to improve the wellness of our Family Medicine residents now and in the future by educating them on more efficient use of our electronic health record (EHR). Resident physician burnout is a significant problem and is correlated with time spent using an EHR after work hours. Family physicians have the highest rate of burnout of all specialties, and the EHR is a significant contributor to this burnout. Studies have shown that increased EHR education can improve job satisfaction. Method: Over 5 months, we provided weekly brief (15 minute) educational sessions covering 6 topics twice and a one-hour individualized meeting of each resident physician with an EHR trainer. We evaluated our intervention with wellness surveys and objective measures of EHR efficiency both pre and post intervention. We further evaluated efficiency by comparing pre and post-intervention values of the following: average keystrokes, mouseclicks, accelerator use, minutes per encounter and percent closed encounters at month's end. Results: Resident questionnaires showed lessons increased knowledge and intention to use EHR accelerators, but this was not statistically significant. Analysis of objective data showed most efficiency metrics worsened, though most not to a degree that was statistically significant. Residents reported subjective increases in efficiency, and paired data from wellness surveys showed an overall decrease in burnout post-intervention vs. baseline. Conclusions: Much of the data in this pilot study does not reach statistical significance, but is highly suggestive that increased EHR training can improve at least perceived efficiency and thereby resident wellness.